Research on Application of Medical Device Real-World Evidence in Regulatory Decisions of the United States - Xiaofang GU; Yuanyuan HOU; Kai LIN; Juenan PAN (Zhongguo yiliao qixie zazhi)
In recent years, with the development of big data application technology, the real-world data and the corresponding generated real-world evidence have attracted the attention of healthcare regulatory authorities around the world. Regulators recognize that real-world research with specific purposes using real-world data can provide important evidence for regulatory decisions. A total of 90 instances of publicly released on the application of real-world evidence to support regulatory decisions of U. S. Food and Drug Administration are explored, and the positioning and value of real-world evidence in U. S. Food and Drug Administration regulatory decisions are summarized and analyzed, providing references for the use of real-world data and real-world evidence to promote medical devices whole cycle regulation in China.